Legislative control over corporate sector - Satish Chander, T. (Jaipur, India : RBSA Publishers, 1994)
With reference to Andhra Pradesh, 1972-1989.
Originally presented as the authors' thesis (Ph. D.--Dept. of Business Management, Osmania University, Hyderabad, 1991) under the title: Controls over state level public enterprises.
Includes bibliographical references (p. [188]-206) and index.
Keywords: Government business enterprises -- India -- Andhra Pradesh